2016
DOI: 10.1002/zaac.201500788
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, Structure, and Characterization of 3, 4′‐Bis‐1H‐1, 2,4‐triazolium Picrate Salt: A New High‐Energy Density Material

Abstract: Abstract. The environmentally friendly high-energy density salt (TRTR)(PA) (TRTR = 3,4Ј-bis-1,2,4-1H-triazole, PA = 2,4,6-trinitrophenol, picric acid) was synthesized and characterized. The X-ray single crystal diffraction results illustrate that the structure of title salt belongs to the monoclinic system, space group P2 1 /c. Many parallel relationships exist in the molecule, as well as a strong intramolecular π-π stacking interaction. The DSC result shows only one exothermal decomposition step at 229.1°C. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 34 publications
0
9
0
Order By: Relevance
“…It is of great significance to analyze and evaluate the thermal safety of energetic compounds to reduce the risks during production, storage, and transportation [29, 30]. The commonly used parameters for thermal safety assessment are self‐accelerating decomposition temperature ( T SADT ) and thermal explosion critical temperature ( T b ) .…”
Section: Resultsmentioning
confidence: 99%
“…It is of great significance to analyze and evaluate the thermal safety of energetic compounds to reduce the risks during production, storage, and transportation [29, 30]. The commonly used parameters for thermal safety assessment are self‐accelerating decomposition temperature ( T SADT ) and thermal explosion critical temperature ( T b ) .…”
Section: Resultsmentioning
confidence: 99%
“…It is observed that the hydrazide layer is twisted to the PA in each structure and shows strong intermolecular H‐bonding network between the N−H protons of hydrazide and –NO 2 groups of PA. The bond distances and angles in the PA anion lie in the expected range as described in the literature for other picrate salts . The selected crystallographic data for salts 1 and 2 obtained from the X‐ray analysis is summarized in Table .…”
Section: Resultsmentioning
confidence: 99%
“…In our work, we have chosen carbohydrazide and oxalyldihydrazide as cations and picric acid (PA) as anion to synthesize new bipicrate salts. The reports describing energetic PA‐based salts are becoming more common in the literature and shown interesting properties for their use in military and civil applications ,,. PA is not widely used in high explosive formulations due to its reactivity toward shell casing metals yielding sensitive metal salts.…”
Section: Introductionmentioning
confidence: 99%
“…As an electron acceptor, the picrate anion may form charge‐transfer molecular complexes with some electron‐donor cation heterocyclic moieties through hydrogen bonding, π–π interactions, and electrostatic interactions. Many organic and inorganic picrate salts have been prepared and studied as energetic materials and optical functional materials . However, none of these salts consist of an azo‐group, diazolium cations, and dipicrate anions.…”
Section: Introductionmentioning
confidence: 99%